Cytotoxicity and vitreous stability of chemically modified connexin43 mimetic peptides for the treatment of optic neuropathy. Issue 7 (20th May 2013) - Chen, Ying‐Shan; Toth, Istvan; Danesh‐Meyer, Helen V.; Green, Colin R.; Rupenthal, Ilva D.
Abstract Optic neuropathy is associated with retinal ganglion cell (RGC) loss leading to optic nerve damage and visual impairment. Unregulated connexin (Cx) hemichannel opening plays a role in RGC loss. Thus, inhibition via Cx43‐specific mimetic peptides (MP) may prevent further cell death. However, the highly hydrophilic character and poor stability of native peptides prevent their efficient delivery across biological membranes. The present study aimed to improve the stability of Cx43 MP by conjugation to C12‐lipoamino acid (C12‐Laa) or sugar groups. Unmodified and modified Cx43 MP were synthesized using solid‐phase peptide synthesis. Their functionality was assessed by propidium iodide (PI) uptake into NT2 cells, a human testicular carcinoma progenitor cell line able to differentiate into astrocytes, whereas the stability in ocular vitreous was measured by reversed‐phase high‐performance liquid chromatography. PI uptake studies showed inhibition of hemichannel opening for unmodified and modified Cx43 MP. Stability measurements revealed improved stability of modified Cx43 MP, with two Laa groups increasing the peptide half‐life in bovine vitreous more than twofold. Conjugation to C12‐Laa or sugar did not affect the functionality of Cx43 MP, but addition of two C12‐Laa groups significantly improved peptide stability. Laa‐modifications may therefore offer improved stability and retinal delivery of peptides in vivo. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:2322–2331, 2013